Geographically-resolved evaluation of economic and environmental services from renewable diesel derived from attached algae flow-ways across the United States - Banks, Austin Brice, author; Quinn, Jason, advisor; Peebles, Christie, committee member; Windom, Bret, committee member (Colorado State University. Libraries, 2022)
Harmful algal blooms (HABs) are becoming more invasive and ever more prevalent due to rises in nitrogen and phosphorus pollution in watersheds. Nitrogen and phosphorus leakages primarily occur from non-point sources like agricultural runoff, but also point sources like wastewater treatment facilities. Previous efforts to reduce nitrogen and phosphorus loadings and mitigate HABs have largely been ineffective despite investment in nutrient reduction technologies. As the population grows, our consumption and dispersal of nitrogen and phosphorus is expected to compound, and HABs will continue to wreak havoc on our aquatic ecosystems. Herein, we introduce a novel biorefinery that taps into the vast sources of nitrogen and phosphorus in watersheds while simultaneously producing biofuels. Contaminated water is diverted to flow over attached algae systems, feeding native, periphytic algal cultures and scrubbing excessive nutrients from the water. Hydrothermal liquefaction converts the algal biomass into renewable fuels, nutrient-rich fertilizers, and carbonaceous char. The evaluation of the biorefinery concept is done through integrating geographically-resolved growth modeling with nutrient resource availability based on all Hydrologic Unit Code-8 (HUC8) in the contiguous US which is integrated into sustainability models to evaluate the economic and environmental impact of the proposed system. Life cycle analysis results demonstrate a global warming potential of 25 g CO2-eq MJ-1, a eutrophication potential of 1.3*10-5 kg N eq MJ-1, and a net energy ratio 0.33 of MJ MJ-1 in the Santa Monica Bay, CA subbasin. Technoeconomic assessments found that renewable diesel can be produced for $1.20 per cubic decimeter (dm-3) or $4.56 per gallon of gasoline equivalent (GGE-1) under optimal conditions in the Santa Monica Bay, CA subbasin, with results dramatically varying across the US. Water quality trading was also incorporated into the analysis. Using modest nutrient credit values of $4.5 per kg of total nitrogen (kg-TN-1) and $4.5 per kg total phosphorus (kg-TP-1) removed enabled the renewable diesel to achieve parity with conventional diesel, $1.01 dm-3 ($3.84 GGE-1) in the Santa Monica Bay, CA subbasin. A more aggressive credit value of $45 kg-TN-1 and $45 kg-TP-1 made the price of the renewable diesel negative in Santa Monica Bay, CA, roughly $-4.45 dm-3 ($-16.8 GGE-1), and across the Midwest, the Gulf of Mexico, and major cities on the East and West Coast. This means the value of the service that the algae provide in remediating watersheds covers all costs of the system to the point where the renewable diesel represents a product with negligible value. These results highlight a path forward for mitigating eutrophication while also creating a sustainable fuel. Discussion focuses on the service that large-scale deployment of attached algae flow-ways provide to remediate excessive nutrients from watersheds and generate biofuels at a cost-effective price point when water quality trading credits are incorporated into the system economics.
Keywords: biofuels; remediation; water quality; life cycle analysis; algae; techno-economic assessment